Determining financial literacy level of university students: The case of Yıldız Technical University - Demir, Tuğba (My University, 2019)
Nowadays, rapid developing technology increases the variety of financial instruments. Therefore, individuals need to have more information before they make a decision. The increase in the financial knowledge level of individuals provides them more savings and gives them the ability to make more solid decisions. Thus, individuals affect not only themselves but the society as well by increasing the level of their own financial literacy. Behaviours of university students on this manner attracts more curiosity considering the fact that their effect on the near future is relatively higher than the other individuals of the society. To that end, we aim to evaluate financial literacy level of university students using 400 undergraduate students as samples from 10 different faculties. According to the results of the survey, the level of financial literacy of male is observed to be higher than that of females.

Özellikle günümüzde teknolojinin daha hızlı ilerlemesi finansal araç çeşitliliğini artırmaktadır. Bu sebeple bireyler karar vermeden önce daha fazla bilgiye sahip olma ihtiyacı duymaktadır. Bireylerin finansal sisteme ait bilgi seviyelerinin artması tasarruflarını artırmakta ve onlara finansal risklere karşı daha bilinçli kararlar alabilme yeteneği sağlamaktadır. Bu sayede finansal okuryazarlık seviyesinin yükselmesiyle bireyler sadece kendilerini değil, toplumu da etkilemektedirler. Toplumun diğer bireylerine göre yakın geleceğe olan etkileri daha yüksek olduğundan, üniversite öğrencilerinin bu konudaki davranışları daha çok merak uyandırmaktadır. Bu çalışma 10 farklı fakülteden 400 lisans öğrencisinin örneklem olarak kullanılması ile hazırlanmış ve bu öğrencilerin finansal okuryazarlık seviyesi ölçülmeye çalışılmıştır. Yapılan anket sonuçlarına göre, erkeklerin finansal okuryazarlık seviyesinin kadınlara göre daha yüksek olduğu gözlenmiştir.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Finansal okuryazarlık; Finansal davranış; Financial literacy; Financial behavior